The Association of Relationship Status and Sex-Life Satisfaction With Body Dissatisfaction and Drive for Muscularity in Male Weight-Lifters - Schneider, Catharina; Bartuschka, Julia; Voracek, Martin; Hennig-Fast, Kristina (Frontiers in Psychology, 2019)
Relationship status and sexuality are linked to body image concerns, but research on the connection to men’s drive for muscularity (DfM) is scarce. Extreme DfM can lead to a pathological preoccupation with muscularity and problematic eating/exercising behavior. This study investigated the relation of relationship status, relationship duration, and satisfaction with sex-life in weight-lifting men via an online survey (N = 270). Using cross-sectional data, we found that single weight-lifting men and those dissatisfied with their sex-life were more dissatisfied with their muscularity and showed stronger DfM than those in a relationship and satisfied men. Longer relationship duration was associated with less dissatisfaction with muscularity and less DfM while relationship satisfaction was not. Thus, being in a relationship and sexual satisfaction are related to less body dissatisfaction and DfM. Further research should use dyadic study designs to investigate both partners exercising and eating behavior in relation to each other.